2015
DOI: 10.3109/13880209.2015.1070879
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of naringin against doxorubicin-induced acute cardiac toxicity in rats

Abstract: Context: Doxorubicin (Dox) is one of the most active chemotherapeutic agents used to treat various types of cancers. Its clinical utility is compromised due to fatal cardiac toxicity characterized by an irreversible cardiomyopathy. Objective: This study evaluates the cardioprotective potential of naringin (NR) against Dox-induced acute cardiac toxicity in rats. Materials and methods: Male Wistar rats were randomly divided into five groups. NR (50 and 100 mg/kg) was administered intraperitoneally (i.p.) daily f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 67 publications
12
54
0
1
Order By: Relevance
“…32,62,63,65 The naringin treatment reduced the catalase activity in the mouse liver which is in agreement with the earlier studies where a similar effect has been reported. 32,[63][64][65] Both the treatment of naringin before or after DOX administration was equally effective in raising the catalase activity in mouse liver in the present study. Likewise, Aegle mamrmelos extract attenuated the doxorubicin-induced alleviation in the catalase activity of mice heart.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…32,62,63,65 The naringin treatment reduced the catalase activity in the mouse liver which is in agreement with the earlier studies where a similar effect has been reported. 32,[63][64][65] Both the treatment of naringin before or after DOX administration was equally effective in raising the catalase activity in mouse liver in the present study. Likewise, Aegle mamrmelos extract attenuated the doxorubicin-induced alleviation in the catalase activity of mice heart.…”
Section: Discussionsupporting
confidence: 81%
“…32,[61][62][63] Naringin treatment has been found to elevate the GSH concentration in the heart and liver of doxorubicin treated mice and rats. 32,[63][64][65] Similarly, extract of Agele marmalos has been reported to elevate myocardial glutathione in mice. 62 Glutamine an amino acid has been reported to protect against the DOX-induced depletion in GSH in rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations